Male Sex Workers Selling Physical Sex during the COVID-19 Pandemic in Portugal: Motives, Safer Sex Practices, and Social Vulnerabilities - Henrique Pereira (Societies, 2021)
The purpose of this research was to assess the motives, safer sex practices, and vulnerabilities of male sex workers who sold physical sex during the COVID-19 pandemic. This study used a mixed strategy, utilizing purposive sampling techniques to conduct 13 online surveys with male sex workers working in Portugal during the COVID-19 pandemic. Participants were aged between 23 and 47 years old and mostly provided their services to other men. Additionally, half of the participants were immigrants. Participants mentioned paying for essential expenses (rent, food, phone, etc.), having money for day-to-day expenses, wanting to, and enjoying it, as their main motives for engaging in sex work. Regarding sexual practices, 3 to 11 participants did not always or did not consistently use condoms during penetrative sex with their clients. Thematic analysis was used to identify the following repeated patterns of meaning regarding COVID-19-related vulnerabilities, encompassing a loss of clients and income, increased work availability, price reductions and negotiation difficulties, emotional functioning, health care access, safer sex negotiations, age, and immigration status. The findings serve as a basis for recommendations regarding social policies aimed at male sex workers who sell physical sex in Portugal.